Enlightenment shadows - Lloyd, Genevieve (Oxford University Press, 2013)
Genevieve Lloyd presents a new study of the place of Enlightenment thought in intellectual history and of its continued relevance. She offers original readings of a range of key texts, which highlight the ways in which Enlightenment thinkers enacted in their writing - and reflected on - the interplay of intellect, imagination, and emotion.